COMPLICATIONS OF CENTRAL-NERVOUS-SYSTEM HYDATID-DISEASE - (:unkn) unknown (KARGER, 1994)
Central nervous system hydatid cyst disease presents with different clinical pictures depending on the involvement of cerebral and spinal structures. The majority of cerebral echinococcosis cases are in the pediatric age group, mostly involving the white matter, and their treatment is mainly surgical. Complications of this entity depend on several factors including the location, size, and multiplicity of the cysts, as well as the presence of contamination. The most common complication is a rupture of the cyst into the subarachnoid space which leads to widespread dissemination followed by severe inflammatory or anaphylactic response. However, vertebral lesions are usually invasive and cause neurological. symptoms due to compression. Almost all patients complain of radicular pain and motor deficits; and up to one half of patients present with paraparesis. This paper examines the natural history and complications which may arise during the treatment of cerebral and vertebral hydatid cysts, and discusses their clinical management.
Keywords: ECHINOCOCCUS; HYDATID CYST; PARASITIC INFECTIONS; CEREBRAL HYDATID CYST; VERTEBRAL HYDATID CYST; SPINAL CORD COMPRESSION; COMPUTERIZED TOMOGRAPHY; CYSTS; BRAIN; ALBENDAZOLE; GROWTH; SPINE; CT